Computer Modelling «Smart Building» - O. Yu. Maryasin; A. S. Kolodkina; A. A. Ogarkov (Моделирование и анализ информационных систем, 2016)
Currently ”Smart building” or ”Smart house” technology is developing actively in industrialized countries. The main idea of ”smart building” or ”smart house” is to have a system which is able to identify definite situations happening in house and respond accordingly. Automated house management system is made for automated control and management and also for organization of interaction between separated systems of engineering equipment. This system includes automation subsystems of one or another engineering equipment as separated components. In order to perform study of different functioning modes of engineering subsystems and the whole system, mathematical and computer modeling needs to be used. From mathematical point of veiw description of ”Smart building” is a continuous-discrete or hybrid system consisting of interacting elements of different nature, whose behavior is described by continuous and discrete processes. In the article the authors present a computer model ”Smart building” which allows to model the work of main engineering subsystems and management algorithms. The model is created in Simulink Matlab system with ”physical modeling” library Simscape and Stateflow library. The peculiarity of this model is the use of specialized management and control algorithms which allow providing coordinated interaction of subsystems and optimizing power consumption.